Do Adult Medicaid Enrollees Prefer Going to Their Primary Care Provider's Clinic Rather Than Emergency Department (ED) for Low Acuity Conditions?. Issue 6 (June 2015) - Capp, Roberta; Camp-Binford, Meredith; Sobolewski, Sarah; Bulmer, Sandra; Kelley, Lauren
Abstract : Background: The rates of annual visits for adult Medicaid enrollees to the emergency department (ED) are increasing. Many programs throughout the country are focused on engaging patients in the use of their primary care providers (PCP) rather than the ED for low acuity conditions. It is unclear, however, the proportion of patients who are willing to use primary care services rather than the ED if they are given the choice. Methods: Cross-sectional study of adult Medicaid enrollees (18 y and older) presenting to a large, urban, academic ED from June to August 2012 with a low acuity condition was performed. We excluded patients who did not have a PCP or active Medicaid insurance. Our primary goal was to determine the proportion of patients who prefer to use the ED, rather than their PCP clinic, if an appointment was immediately available. Our second goal was to understand why patients would prefer ED over PCP care. Results: A total of 150 patients agreed to complete the survey, and 95 (63.3%) met our inclusion criteria. Forty-three patients (45.3%) stated preferring to use their PCPs rather than the ED if an appointment was available at that time. Thirteen (48.1%) cited that the ED had more technology or specialty care services available when compared with their PCP's clinic, 8 (15.4%) were in significant pain, and 6 (11.5%) felt the care they received in the ED was better than what they would receive in their PCP clinic. Conclusions: Our study shows that a little less than half of adult Medicaid enrollees presenting to the ED with low acuity conditions would have preferred to use their PCP rather than the ED, if an appointment had been immediately available.